Penggantian Calon Legislatif Terpilih Dalam Pemilihan Umum Oleh Partai Politik Sebelum Pelantikan Menurut Perspektif Peraturan Perundang-Undangan - Mayasari, Vevryka; Hartati, Hartati; Zarkasi, A. (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The party serves as a strategic intermediary between the process of government and the people. Many assert that political parties essentially dictate democracy. Quoted from the Association for elections and democracy (Perludem) explained that in the 2024 legislative general election there were many replacements for elected legislative candidates by the bearer party for unclear reasons. Replacing elected candidates before inauguration is on the rise, likely because it is easier to do so than after inauguration. However, this practice distorts popular sovereignty because it contradicts the open proportional electoral system, which states that the candidate with the most votes must be the one who holds office. From the legislative side, the issues that will be discussed in this study are the legality and procedures for replacing legislative candidates elected by political parties in the general election before the inauguration. According to the findings of the study, the Basic Rules of political parties (AD) and household rules (ART) govern the process of dismissing party members, allowing them to replace elected legislative candidates in presidential elections. There is a gap in the entry of certain interests in the dismissal of members of political parties. First, the party Governing Council at the regional level can propose the dismissal of party members, the regional-level party Governing Council has the right to propose the names of party members to be dismissed. Second, the party's Central Governing Council no longer re-verifies the proposal and immediately issues a direct determination.